2004
DOI: 10.1093/pasj/56.5.753
|View full text |Cite
|
Sign up to set email alerts
|

Chandra Observation of a Group of Galaxies HCG 80: Does the Spiral-Only Group Have Hot Intragroup Gas?

Abstract: We present an analysis of Chandra X-ray observations of a compact group of galaxies, HCG 80 (z = 0.03). The system is a spiral-only group composed of four late-type galaxies, and has a high-velocity dispersion of 309 km s −1 . With high-sensitivity Chandra observations, we searched for diffuse X-ray emission from the intragroup medium (IGM); however, no significant emission was detected. We place a severe upper limit on the luminosity of the diffuse gas as L X < 6 × 10 40 erg s −1 . On the other hand, signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…If we use the spectral results and attribute the emission modelled with a plasma spectrum to a hot ISM, we can derive an average gas density of n e ∼ 7.5×10 −3 cm −3 and a total mass of M gas ∼ 3×10 8 M in the hot phase, under a simple assumption of a spherical distribution within r ∼ 7.5 kpc. This is ∼10× lower than what is detected in the neutral cold phase (H i Pompei et al 2007), but relatively high with respect to the hot ISM detected in the disk and halos of star-forming late type galaxies (Tüllmann et al 2006) and comparable to the amount of hot gas detected in HCG80a (Ota et al 2004).…”
Section: Individual Galaxiesmentioning
confidence: 55%
See 1 more Smart Citation
“…If we use the spectral results and attribute the emission modelled with a plasma spectrum to a hot ISM, we can derive an average gas density of n e ∼ 7.5×10 −3 cm −3 and a total mass of M gas ∼ 3×10 8 M in the hot phase, under a simple assumption of a spherical distribution within r ∼ 7.5 kpc. This is ∼10× lower than what is detected in the neutral cold phase (H i Pompei et al 2007), but relatively high with respect to the hot ISM detected in the disk and halos of star-forming late type galaxies (Tüllmann et al 2006) and comparable to the amount of hot gas detected in HCG80a (Ota et al 2004).…”
Section: Individual Galaxiesmentioning
confidence: 55%
“…The X-ray properties appear also very similar: all 4 galaxies are detected as individual sources (both due to the AGN and starburst activity) already by the ROSAT satellite (Saracco & Ciliegi, 1995;Ponman et al, 1996;Dos Santos & Mamon, 1999), while the diffuse emission recently characterised with XMM-Newton has a comparable luminosity but slightly higher best fit temperature (∼ 0.5 keV, although within the uncertainties; note that the ROSAT data suggested a cooler temperature of 0.27 keV Dos Santos & Mamon, 1999) than SCG0018-4854. Only two other systems, with a spiral fraction of ∼ 1, have been studied with Chandra or XMM-Newton: HCG 80 (Ota et al, 2004) was not detected by Chandra, with an estimated limit to the luminosity of the diffuse component at L x ∼ 6 × 10 40 h −2 70 erg s −1 , in spite of the larger velocity dispersion (σ v ∼ 300 km s −1 ) of the system; low level diffuse emission is measured in recent XMM-Newton images of the Cartwheel, again at similar luminosities and gas temperatures (Crivellari et al, in preparation).…”
Section: Scg0018-4854 In Contextmentioning
confidence: 99%
“…It is known that galaxy groups exhibit rather large scatter in their gas richness (Osmond & Ponman 2004), with spiral-rich ones tending to be particularly gas poor (Ota et al 2004). From equation (15), we may then speculate that a galaxy group borne as a relatively gas-rich system is subject to a fast merger process, while it remains otherwise an ordinary group.…”
Section: Discussionmentioning
confidence: 97%
“…The pioneering work of Zabludoff (1999) suggested that groups might fall into different classes defined by their X-ray properties: from groups with a luminous, extended, hot IGM centred on a giant E to groups with little or no diffuse emission. Several examples of these classes can now be found in the literature (see e.g., Mulchaey et al 2003;Trinchieri et al 2003;Belsole et al 2003;Ota et al 2004). In a hierarchical evolutionary scenario, the final product of a merged group would be a luminous isolated E with an extended X-ray halo, and a few have indeed been identified (see e.g., Mulchaey & Zabludoff 1999;Vikhlinin et al 1999;Jones et al 2003;Khosroshahi et al 2004).…”
Section: Introductionmentioning
confidence: 95%